2017
DOI: 10.1371/journal.ppat.1006384
|View full text |Cite
|
Sign up to set email alerts
|

MHC Ib molecule Qa-1 presents Mycobacterium tuberculosis peptide antigens to CD8+ T cells and contributes to protection against infection

Abstract: A number of nonclassical MHC Ib molecules recognizing distinct microbial antigens have been implicated in the immune response to Mycobacterium tuberculosis (Mtb). HLA-E has been identified to present numerous Mtb peptides to CD8+ T cells, with multiple HLA-E-restricted cytotoxic T lymphocyte (CTL) and regulatory T cell lines isolated from patients with active and latent tuberculosis (TB). In other disease models, HLA-E and its mouse homolog Qa-1 can act as antigen presenting molecules as well as regulators of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 62 publications
0
40
0
Order By: Relevance
“…For example, MR1 presents vitamin B metabolites, which are unique to bacteria and yeast ( Kjer-Nielsen et al, 2012 ), and M3 binds N-formylated peptides of mitochondrial or prokaryotic origin ( Wang et al, 1991 ). We, therefore, focused on three non-classical molecules, namely, CD1d, Qa-1, and Qa-2, which have been shown to present pathogen-derived antigens ( Fischer et al, 2004 ; Bian et al, 2017 ; Swanson et al, 2008 ; Shang et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…For example, MR1 presents vitamin B metabolites, which are unique to bacteria and yeast ( Kjer-Nielsen et al, 2012 ), and M3 binds N-formylated peptides of mitochondrial or prokaryotic origin ( Wang et al, 1991 ). We, therefore, focused on three non-classical molecules, namely, CD1d, Qa-1, and Qa-2, which have been shown to present pathogen-derived antigens ( Fischer et al, 2004 ; Bian et al, 2017 ; Swanson et al, 2008 ; Shang et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…immunoregulatory activities of HLA-E restricted T cells was also found for the T-cell clones [14,22]. Not only the cytolytic effector functions but also the immunoregulatory properties of HLA-E restricted cells may be important in relation to protective immunity, by controlling pathogenic inflammation [23]. A negative consequence may be that immunoregulation contributes to pathogen persistence and chronic infection [11,30].…”
Section: Discussionmentioning
confidence: 94%
“…In subsequent work we demonstrated that HLA-Erestricted clonal CD8 + T cells were able to inhibit Mtb outgrowth in infected human macrophages [22]. Qa-1, the mouse homolog of HLA-E, can also present Mtb derived antigens during infection [23]. Mice that lack Qa-1, are more susceptible to Mtb infection and this increased susceptibility to progress to disease was due to dysregulated T-cell responses [23].…”
Section: Introductionmentioning
confidence: 99%
“…Their varying amino acid length implies that HLA-E has higher peptide binding plasticity than solely the VL9 peptide [75]. These non-canonical T cells contribute to the majority of T cells present during active Mtb infection [77], and overshadow T cells restricted by canonical HLA class Ia epitope presentation [78,79]. Mtb antigens presented by HLA-E to CD8 + T cells can induce either a cytotoxic or regulatory phenotype, consequently inhibiting Mtb pathogenesis and growth in infected macrophages [7,78].…”
Section: Mycobacterium Tuberculosismentioning
confidence: 99%
“…These non-canonical T cells contribute to the majority of T cells present during active Mtb infection [77], and overshadow T cells restricted by canonical HLA class Ia epitope presentation [78,79]. Mtb antigens presented by HLA-E to CD8 + T cells can induce either a cytotoxic or regulatory phenotype, consequently inhibiting Mtb pathogenesis and growth in infected macrophages [7,78]. HLA-E : Mtb-restricted T cells from active TB infection express a type 2 cytokine profile with increased interleukin (IL)-4 and IL-10 production, and assist B cells with antibody and cytokine production to inhibit Mtb growth [65,76,77].…”
Section: Mycobacterium Tuberculosismentioning
confidence: 99%